Pengaruh Bentuk Bukaan Atap Bangunan Terhadap Tingkat Kenyamanan Termal Pada Rumah Panjang Suku Dayak Brusu, Kecamatan Sekatak, Kalimantan Utara - Wahyudi, Eko (Borneo Engineering : Jurnal Teknik Sipil, 2018)
The long house of the Brusu Dayak tribe that lives in North Kalimantan is a house that always increases the length of the building following the increase in the number of family heads in one offspring. The most interesting part of the longhouse compared to other Dayak tribes' houses is that in the longhouse Brusu Dayak tribes do not have windows but only rely on openings on the roof of the building according to their residential needs so that it affects the thermal comfort of the longhouse. In general, this study aims to determine the effect of the shape of openings on the roofs of Dayak Brusu tribal longhouse buildings on thermal comfort levels. The research method includes direct surveys to the field by observing the shape of the building and the shape of the roof opening in the longhouse, as well as doing direct measurements on several points determined. Measurements made include measurements of temperature, humidity, air movement, where measurements are made on the interior of a long house with 15 measuring points, where each point is measured for 24 hours with the time of measurement every 2 hours. From the above analysis, it can be concluded that the effective temperature for the tenang area is more likely to be lower than the ganak and lamin, this is because the roof formation of the long house located in the garden can be opened and closed according to the needs of the occupants.